Understanding perception and action in sport: how can virtual reality technology help? - Craig, C. (Sports Technology, 2013)
Although technology can facilitate improvements in performance by allowing us to understand, monitor and evaluate performance, improvements must ultimately come from within the athlete. The first part of this article will focus on understanding how perception and action relate to performance from two different theoretical viewpoints. The first will be predominantly a cognitive or indirect approach that suggests that expertise and decision-making processes are mediated by athletes accruing large knowledge bases that are built up through practice and experience. The second, and alternative approach, will advocate a more "direct" solution, where the athlete learns to "tune" into the relevant information that is embedded in their relationship with the surrounding environment and unfolding action. The second part of the article will attempt to show how emerging virtual reality technology is revealing new evidence that helps us understand elite performance. Possibilities of how new types of training could be developed from this technology will also be discussed.